The Borders of the Law: Legal Fictions, Elusive Borders, Migrants’ Rights - Molinari, Caterina (2022)
Bordering processes take place through different means and are carried out by different actors. Laws and regulatory activities have a prominent place among border-drawing instruments: Their capacity to mobilise actors, allocate funds, and determine procedures and remedies make them a formidable and multifaceted bordering tool. It is therefore not surprising to notice that EU institutions have heavily relied on regulatory tools when the need to resort to new bordering processes emerged in the aftermath of the so-called migration crisis. This article delves into a particular (re-)bordering process emerging from the legislative proposals attached to the Commission’s 2020 New Pact on Migration and Asylum: the attempt to uncouple the duty to fully respect and protect fundamental rights from the reality of migrants’ presence on national territory. This objective is pursued by the proposed legislative package through non-entry fictions, capable of untangling the legal notion of “border” from its physical reality for the purpose of immigration law (only). The analysis of the relevant provisions provides the reader with a number of insights into the transformation of EU borders. First, borders (as defined by the law) are subject to a peculiar legal regime. Secondly, the legal notion of borders is increasingly independent of its physical/geographical correspondence. Thirdly, legal border lines are not linked to any place on the ground, but rather follow irregular migrants as they move, confining them to areas of less law, no matter their location.